Meningkatkan Kemampuan Kosakata Anak Usia 3-4 Tahun Menggunakan Media Cardbox - Karen Steivy Lanie, Gracia; Wijayaningsih, Lanny (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This research is motivated by a problem related to children with limited vocabulary skills, so it requires the use of media to improve children's vocabulary skills in speaking. This study aims to answer the problems (1) How can the results of the learning process using cardbox media improve the vocabulary skills of children aged 3-4 years ?. This article is discussed through Classroom Action Research (CAR) which is carried out through two cycles, with each stage consisting of planning, action, observation and reflection stages. This research data obtained through observation and documentation. The subjects of this study were PAUD children in Daudolu Village, East Nusa Tenggara, totaling 5 children. This research was conducted in January – April 2021. The results showed that cardbox media conducted in two cycles was proven to improve the vocabulary skills of children aged 3-4 years at PAUD Maranatha school. This can be seen from the improvement in every aspect of the research. In the first cycle, there was one meeting and the second cycle was carried out in one meeting. The result of children's vocabulary skills in the pre-cycle was 45%, increased in cycle 1 to 50% and increased in cycle 2 90%. From the results of the study, it can be concluded that the vocabulary skills of children aged 3-4 years from stage to stage can be increased using cardbox media.